REDESIGN OF BREASTFEEDING CHAIR FOR NURSERY ROOM - Prima F; Vella V; Lusi S; Hilma Raimona Z (Malaysian Journal of Public Health Medicine, 2020)
Breastfeeding chair is one of the essential facilities in the airport. This study designs the breastfeeding chair for the nursery room in Minangkabau International Airport. Quality Function Deployment (QFD) was used to investigate the customer requirements by distributing questionnaires to 100 mothers in Padang West Sumatra. Anthropometry data was also measured form those respondents. The study resulted in a design of ergonomic breastfeeding chair which was used features obtained from the voice of the customers. The design has considered the condition of the mother giving birth by normal as well as a cesarean. The design has an adjustable back seat with an angle of 95o,105o, and 110o; it has an adjustable footrest with 120o, 140o, and 180o angles. The chair has a headrest, baby support pad, a portable baby cushion, an adjustable baby bearings. The chair has also equipped with an assemble torn neck, a small drawer on the side of the chair, and a palm rest that can be used or not by adjusting the height.